FORMULASI DAN UJI STABILITAS GUMMY CANDIES BUAH NAGA (Hylocereus polyrhizus) DENGAN VARIASI KONSENTRASI GELATIN DAN KARAGENAN SEBAGAI GELLING AGENT - Rashati, dewi -; Eryani, Mikhania Christiningtyas (Jurnal Informasi Kesehatan Indonesia (JIKI), 2019)
Gummy candies is semi wet chewing candies that made from gelatin and carageenan. The aim of this study was to formulated Hylocereus polyrhizus to gummy candies form. Variaton concetration of gelatin and carageenan in this study were 750 mg : 250 mg (F1), 500 mg : 500 mg (F2) dan 250 mg : 500 mg (F3). The method used was molding method. Gummy candies were evaluated organoleptic, weight variaton, pH and stability at cool, cold and warm temperature. The results showed that all formulas sweet, clear brown, and had tutty fruty smell. The elasticity of F1 was little chewyy, chewy and very chewy. All formulas meet the requirement of weight variation. All formualas had 4 of pH. Based on stability study, F3 at cold temperature was the most stable formula.